Correlation Between Chemotherapy-Induced Nausea and Vomiting with Quality of Life in Patients with Ovarian Cancer at Dr. Cipto Mangunkusumo Hospital - Madjid, Veinardi; Calvin, David; Purwoto, Gatot; Utami, Tofan Widya; Anggraeni, Tricia Dewi; Vidiawati, Dhanasari; Winarto, Hariyono (UI Scholars Hub, 2024)
Introduction: Nausea and vomiting (NV) remain as side effects of chemotherapy, which has a detrimental effect on patients’ quality of life (QOL) and treatment adherence. This study aimed to determine the effect of chemotherapy-induced NV (CINV) on the QOL of patients with ovarian cancer treated with chemotherapy at Dr. Cipto Mangunkusumo Hospital (CMH). Methods: We conducted a cross-sectional study in patients with ovarian cancer receiving first-line chemotherapy regimens of carboplatin and paclitaxel. The European Organisation for Research and Treatment helped translate the Quality-of-Life Questionnaire-OV28 (QLQ-OV28) into Indonesian and tested it in a preliminary study. The approved Indonesian version of the QLQ-OV28, with the Quality-of-Life Questionnaire-C30 (QLQ-C30), was then used to evaluate QOL before and 1 week after chemotherapy. Results: Several symptom scales increased, whereas function scales decreased. Moreover, 72.5% had an increase in the NV symptom scale, whereas 67.5% had a decrease in patients’ scale after chemotherapy. CINV had a significant partial effect on reducing QOL (p = 0.047 and y = 12.208–0.432). Conclusions: CINV has a significant influence on lowering the QOL of patients with ovarian cancer undergoing first-line chemotherapy regimens with carboplatin and paclitaxel in CMH.